Priority Factors Determining the Income of Woven Fabric Craftsmen in Sumbawa Regency: Process Hierarchy Analysis Approach - Arfina Durratul Hikmah; Muhammad Nurjihadi (Buletin Antropologi Indonesia, 2025)
This article discusses the most dominant factors in the income of woven fabric craftsmen. The aim of this research is to determine the priority weight of factors that determine the income of woven fabric craftsmen in Sumbawa Regency. The research method used is quantitative using primary data. Data analysis was carried out using the Analytical Hierarchy Process (AHP), criteria and alternative procedures in AHP were obtained from references. Based on the results of previous research, the revenue criteria are increasing efficiency, increasing productivity and increasing competitiveness. Meanwhile, the alternatives from this research are work experience, education, working hours and age which influence the income of woven fabric craftsmen. Based on the results of global priority weighting in the AHP procedure, it is known that the most dominant factor influencing income is work experience with a weight of 40.98%, age with a weight of 23.04%, working hours with a weight of 20.30%, education with a weight of 15.69%.